Indicadores de qualidade na Educação : um estudo a partir do PISA e da TALIS - Corradini, Suely Nercessian (Universidade Federal de São Carlos, 2012)
International Student Assessment) and the results presented by TALIS (Teaching and Learning International Survey), considering the configuration of schools highly evaluated and the practices developed in those institutions. Concerning that matter, two questions were designed as guidelines for the research process: (1) What is the configuration of the schools that performed well in PISA 2009, in São Paulo, according to the TALIS / PISA? (2) What kind of practices are developed in those schools? Considering those questions as a starting point, the procedures of one public and two private schools in the State of Sao Paulo were examined. Those institutions were chosen due to their good scores in PISA 2009. Matching the PISA 2009 modus operandi, the results obtained in reading were selected as the core of our analysis. Three specific objectives were established to shape the procedures followed in this research: (1) analyze the elements that influence the educational performance of students by focusing essentially on the features of their formation, (2) identify the characteristics of teachers and schools by assessing TALIS results, and (3) analyze the opinion of teachers and institution managers on PISA, TALIS and students performance. The current objectives are accomplished by adopting a quantitative-qualitative methodological research approach. The data consist of interviews with the general coordinator of PISA 2009 in Brazil and with directors / coordinators of the selected schools; visits to the focus schools; analysis of a collection of questions from PISA answered by students and directors and analysis of TALIS questionnaires answered by the director and teacher participants. This investigation is justified, therefore, by the potentiality it offers to the understanding of the contributions of PISA and TALIS results to the formulation of public policy and education management in Brazil and its implications for the educational system and schools. It was attainable by analyzing the organization of schools with good performance in PISA in Sao Paulo, considering such aspects as components of quality indicators. Within this context, the results of those large-scale measurement instruments raise important issues, since they acknowledge only a small number of "high quality schools" contrasted with a great number of units, especially public, marked by insufficient and below expectation performance. Further than analyzing the schools based on the results from PISA and TALIS, the outcome of this research invites for reflection on the practices adopted by schools and their relation to the results verified by the focused instruments.
Keywords: Educação; Indicadores de qualidade; Leitura; PISA; TALIS; Education; quality indicator; reading; PISA; TALIS; CIENCIAS HUMANAS::EDUCACAO